Establishment of an abnormal vascular patterning model in the mouse retina - Akane Morita; Shohei Sawada; Asami Mori; Shiho Arima; Kenji Sakamoto; Tohru Nagamitsu; Tsutomu Nakahara (Elsevier, 2018)
Abnormalities in retinal blood vessels and neuronal function persist in eyes undergoing retinopathy of prematurity. In this study, we examined morphological and functional changes in retinal blood vessels and neurons in mice that had undergone short-term interruption of retinal vascular development through inhibition of vascular endothelial growth factor (VEGF) signaling. In mice treated with the VEGF receptor tyrosine kinase inhibitor KRN633 on postnatal day (P) 0 and 1, the vascular density in the retinal surface increased by P12, but development of deep retinal vascular plexus and choroidal vasculature was delayed until P14. Overall retinal morphology was mostly normal in KRN633-treated mice during the observation period (∼P28), with the exception of P8 and P14. On P28, abnormalities in retinal vascular patterns were evident, but electroretinogram and retinal blood perfusion were within the normal range. Abnormal architecture of retinal vasculature disturbs retinal hemodynamics; therefore, mice treated postnatally with VEGF receptor inhibitors could serve as an animal model for studying the regulatory mechanism of local retinal blood flow and the effect of persistent abnormal retinal vascular patterns on the risk of onset of retinal ischemia. Keywords: Endothelial cell, Neuronal cell, Vascular endothelial growth factor, Vascular patterning, Retina